Quality and Women-Centered Care in Comprehensive Abortion Care (CAC) WHO 2024: Literature Review - Yulizawati, Yulizawati; Mayasari, Shinta; Yulika, Marzatia; Pramawahyudi, Pramawahyudi; Qalbi, Tajri Syayidil; Intasir, M. Pemberdi (Journal of Midwifery, 2025)
Abortion care is an integral component of women's reproductive health services. Comprehensive Abortion Care (CAC), as outlined by the WHO, emphasizes not only clinical safety but also women-centered care that respects women's rights, experiences, and autonomy. This literature review aims to synthesize current evidence on the quality of care and the implementation of women-centered care within CAC services. A literature review was conducted using PubMed and Semantic Scholar, focusing articles published between 2020 and 2025. Fourteen studies meeting the inclusion criteria were analyzed through thematic synthesis. The findings indicate that women's satisfaction with abortion and post-abortion services is strongly influenced by interpersonal aspects of care, including respectful communication, empathy, emotional support, and involvement in decision-making. While many health facilities demonstrate adequate technical quality, gaps persist in the consistent delivery of women-centered care due to system readiness, stigma, legal constraints, and variability in provider attitudes. Evidence from interventional studies suggests that structured person-centered care models can significantly improve women's care experiences. This review highlights that high-quality CAC extends beyond clinical outcomes and requires deliberate integration of women-centered principles into routine practice. Strengthening provider competencies and health system support is essential to ensure equitable, respectful, and meaningful abortion care.